The complete mitochondrial genome of the hybrid of Pagrus major (♀) × Acanthopagrus schlegelii (♂). (3rd July 2016) - Zhu, Fei; Zhang, Zhiyong; Chen, Shuyin; Zhang, Zhiwei; Xu, Jin; Jia, Chaofeng; Yin, Shaowu; Zhang, Guosong
Abstract: The complete mitochondrial sequence of the hybrid from red bream ( Pagrus major ♀) × black porgy ( Acanthopagrus schlegelii ♂) was firstly determined by using the PCR-based method. The total length of the mitogenome genes of the hybrid was 17 028 bp in accordance with red bream, and it contained 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes and one control regions. Compared with the complete mitochondrial genome of its parents, the results showed that the hybrid of P. major (♀) × A. schlegelii (♂) was consistent with a maternal inheritance. All protein initiation codons are ATG, except for COX1 that begins with GTG. The complete mitogenome of the hybrid of P. major (♀) × A. schlegelii (♂) provides an important data set for the exploration of mitochondrial inheritance mechanism.